Factors Influencing Successful Employment for Men With Visual Impairment - Menik Budiarti (The Center for Disability Studies and Services Brawijaya University, 2018)
Introduction: This study investigated experiences of men with visual impairment in Indonesia as they responded to challenges in employment. Method: The study was qualitative, using in-depth interviews.Â The participants were employed men with visual impairment and married to a sighted woman, selected using snowball sampling. The visual impairment was acquired before employment and marriage, but no specific exclusion criteria for the visual impairment. Thirty-nine participants were interviewed for one hour each in their native language of Bahasa Indonesia using semi-structured questions. The interviews were transcribed, translated, and analysed. Results: Five factors and seventeen sub factors were found: institutional settings, family support, social support, personal traits, and employment arrangements. Discussion: The study found that there are factors that play a positive role for some participants, but a negative role for others. Improvement in certain factors is needed in order to develop better employment for people with visual impairment in Indonesia. Limitations of this study were: the number of participants, the locations of study, and the criteria of visual impairment. Implications for Practitioners: Improving the education system, optimal implementation of the employment quota system, developing personal traits, and improving awareness to trigger better family and social network support, would be beneficial for future employment of people with visual impairment.